Improvement of advanced postvaccinal demyelinating encephalitis due to plasmapheresis - Andreas Rogalewski (Dove Medical Press, 2007)
Andreas Rogalewski1, Jörg Kraus3, Martin Hasselblatt2, Christoffer Kraemer1, Wolf-Rüdiger Schäbitz11Department of Neurology; 2Institute of Neuropathology, University of Muenster, Germany, 3Paracelsus Private Medical University and Salzburger Landesklinken, Christian-Doppler-Klinik, Department of Neurology, Salzburg, AustriaAbstract: We report a case of acute demyelinating encephalitis that occurred after viral vaccination against hepatitis A-, hepatitis B-, and poliovirus and vaccination against bacterial toxins of diphtheria and tetanus. After different diagnosis had been excluded, we diagnosed postvaccinal demyelinating encephalitis and started treatment with high dose intravenous methylprednisolone, followed by peroral application in decreasing dosages for three weeks. A few days after the treatment with methylprednisolone had been finished, the patient’s medical condition deteriorated again. Thus, we initiated plasma exchange at an advanced state of illness, which led to significant continuous improvement. The role of plasma exchange is discussed controversially, in particular the issue of timing. We report a case that shows improvement due to plasmapheresis several weeks after symptom onset.Keywords: ADEM, vaccination, encephalitis, plasmapheresis, demyelination, plasma exchange